Role of Environmental Education in Adopting Pre-Emptive Measures of Smog in Urban Areas of South Punjab, Pakistan: A Policy Review - Nadeem, M. Asif; Bajwa, Muhammad Jamil; Bajwa, Ifrah Jamil (Pakistan Languages and Humanities Review, 2024)
This article investigates smog prevention and mitigation policy strategies as well as the role of environmental education to adopt preemptive measures in Pakistan. Inhabitants of South Punjab (Pakistan) suffer from severe air pollution as a result of urbanization, industrialization, and agricultural practices. Existing literature on the effects of smog in metropolitan settings, as well as measures undertaken elsewhere, were evaluated. Specific challenges such as crop residue burning, automobile, industrial pollutants and interior air quality impacting smog levels were emphasized in case studies. Current environmental education programs in the region, as well as factors impacting learning, were also evaluated. The research concluded that environmental education, source reduction through rules, incentives, and community engagement are all necessary to combat pollution. Opportunities to enhance policies aimed at industries such as brick kilns and boost public acceptability of efforts remain. Environmental stewardship may be boosted through improved educational infrastructure and creative teaching practices.